2014
DOI: 10.1097/opx.0000000000000316
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ambient Light and Age-Related Macular Degeneration on Precision Walking

Abstract: While walking performance is similar between groups in normal light, poor ambient lighting results in decreased foot placement accuracy in older adults with AMD. Improper foot placement while walking can lead to a fall and possible injury. Thus, to improve the mobility of those with AMD, strategies to enhance the environment in reduced lighting situations are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 39 publications
1
21
0
9
Order By: Relevance
“…DIF analysis comparing glaucoma patients with and without AMD demonstrated that patients with glaucoma and AMD had greater difficulty walking on uneven ground, using stairs and judging distances of foot to step/curb than those without AMD. These findings support work by Alexander et al, who demonstrated that patients with AMD had increased difficulty when negotiating a curb and poorer gait precision in lower ambient light levels compared with normal subjects. As both AMD and visual field loss from glaucoma increase the risk of falling among older adults, it is understandable that the combination of both conditions leads to a heightened awareness of hazardous gait.…”
Section: Discussionsupporting
confidence: 90%
“…DIF analysis comparing glaucoma patients with and without AMD demonstrated that patients with glaucoma and AMD had greater difficulty walking on uneven ground, using stairs and judging distances of foot to step/curb than those without AMD. These findings support work by Alexander et al, who demonstrated that patients with AMD had increased difficulty when negotiating a curb and poorer gait precision in lower ambient light levels compared with normal subjects. As both AMD and visual field loss from glaucoma increase the risk of falling among older adults, it is understandable that the combination of both conditions leads to a heightened awareness of hazardous gait.…”
Section: Discussionsupporting
confidence: 90%
“…People with AMD walked slowly and cautiously during light and dark adaptation, while fully sighted people only behaved in this way during dark adaptation, indicating that those with healthy vision respond during dark adaptation as though their vision were impaired 48. People with AMD walk more cautiously, make more gait modifications while walking on altered surfaces47 and have difficulty stepping on low contrast targets in dim light and during dark adaptation 49. AMD affects navigating paths under low lighting51 and curb navigation particularly during dim lighting and dark adaptation 50.…”
Section: Resultsmentioning
confidence: 99%
“…Visual information is a crucial sensory input that facilitates safe walking. A number of studies have shown associations between diminished or abnormal visual input and decrements in walking performance, including during control of steady state walking (Helbostad et al, 2009 ; Swenor et al, 2014 ) and during more complex tasks like obstacle crossing and curb negotiation (Alexander et al, 2014a , b ; Novak and Deshpande, 2014 ). This may be due in part to impaired automaticity of walking.…”
Section: Mechanistic Factors That Influence Automaticitymentioning
confidence: 99%